Improved optical damage threshold graphene Oxide/SiO2 absorber fabricated by sol-gel technique for mode-locked erbium-doped fiber lasers. (April 2019) - Chen, Zhendong; Wang, Hongying; Wang, Yonggang; Lv, Ruidong; Yang, Xiguang; Wang, Jiang; Li, Lu; Ren, Wei
Abstract: In this study, a mode-locked erbium-doped fiber (EDF) laser based on solid-state graphene oxide (GO)-doped sol-gel glass saturable absorber (SA) was designed and tested. The GO-based SA was fabricated for the first time using low-temperature sol-gel technique. Compared to traditional ways of fabricating SAs, the SAs-doped sol-gel glass showed outstanding advantages in terms of high optical damage threshold. The optical damage threshold of SAs-doped sol-gel glass reached as high as 50.69 GW/cm 2 . X-ray diffractometry (XRD), infrared spectroscopy (IR), scanning electron microscopy (SEM) and annex-energy spectrometry (EDS) identified the main component of prepared sol-gel glass as compact amorphous silicon dioxide. The application of GO-doped sol-gel glass to EDF laser yielded stable mode-locked fiber laser operation. The pulse duration, maximum output power and peak power were recorded as 582 fs, 17.58 mW and 1.30 kW, respectively. Overall, these data indicated that the proposed sol-gel method is promising for fabricating practical SAs for mode-locked fiber lasers. Graphical abstract: Image 1